Analisis Kekuatan Campuran Aspal Panas (AC-BC) dengan Variasi Kadar Limbah Plastik Multilayer Melalui Pengujian Marshall - Rizki Ridho Sanggara; Anwar Efendy; Nurul Hidayati (Jurnal Talenta Sipil, 2026)
The increasing volume of multilayer plastic waste, which is difficult to recycle, has encouraged the exploration of alternative applications in road construction materials. This study aimed to analyze the effect of multilayer plastic waste content on the Marshall characteristics of Asphalt Concrete–Binder Course (AC-BC) mixtures and to determine the optimum plastic content that provides the best mixture performance. An experimental laboratory method was employed using the Marshall test on AC-BC mixtures with an optimum asphalt content (OAC) of 5,15% and multilayer plastic waste contents of 3%, 4%, 5%, 6%, and 7% by asphalt weight. The evaluated parameters included stability, flow, Void in Mix (VIM), Void in Mineral Aggregate (VMA), Void Filled with Bitumen (VFB), and Marshall Quotient (MQ). The results indicated that all multilayer plastic variations produced stability values ranging from 1076 to 1262 kg, flow values from 3.10 to 3.53 mm, and Marshall Quotient values from 309 to 386 kg/mm, all of which satisfied the 2018 Bina Marga General Specifications. The VMA values ranged from 16.57% to 17.57%, while VFB values ranged from 67.43% to 72.39%. The VIM values ranged from 4.57% to 5.72%, with the 5%, 6%, and 7% mixtures slightly exceeding the maximum specification limit. The 4% multilayer plastic content exhibited the best performance, producing the highest stability value of 1262 kg while satisfying all Marshall parameters. These findings demonstrate that multilayer plastic waste has strong potential as an alternative additive in AC-BC mixtures to improve pavement performance while supporting sustainable plastic waste management.